Sea-level and surface-water change in the western North Atlantic across the Oligocene-Miocene Transition: A palynological perspective from IODP Site U1406 (Newfoundland margin) - Egger, Lisa M.; Bahr, André; Friedrich, Oliver; Pross, Jörg (Marine micropaleontology, 2018)
The Oligocene-Miocene transition (OMT; ~23.1Ma) terminates the late Oligocene warming trend and is marked by a transient, large-amplitude expansion of Antarctic ice sheets. The associated glacial maximum, which is expressed by a ~1‰ positive shift in benthic foraminiferal oxygen-isotope values, is commonly referred to as the ‘Mi-1 isotope event’. Whereas the causes for the glacial maximum at the OMT are intrinsically connected to Southern Hemisphere ice-sheet dynamics, the behavior of the surface ocean in the Northern Hemisphere during this time is poorly known. To contribute to a better understanding of the paleoceanographic evolution during the OMT in the higher-latitude North Atlantic, we have analysed both marine and terrestrial palynomorphs from Integrated Ocean Drilling Program (IODP) Site U1406 offshore Newfoundland; this site has yielded a complete OMT section and exhibits a high-quality magnetostratigraphy that provides precise age control and allows reliable correlation to other records beyond Newfoundland. Our palynological data, which span the interval from 23.3 to 22.5Ma and have a mean temporal resolution of 11.9kyrs, show strong ~110-kyr eccentricity-paced oscillations during the earliest Miocene; these oscillations are in phase with similar cyclicity identified in previously published benthic foraminiferal oxygen-isotope records. More specifically, a pronounced sea-level variability is documented by the abundances of neritic dinoflagellate cysts (dinocysts) and terrigenous palynomorphs, which both reach maxima during peak glacial intervals as inferred from previously published South Atlantic benthic oxygen-isotope data. A decline in the abundance of warmer-water dinocysts suggests a surface-water cooling offshore Newfoundland from the latest Oligocene onwards. Surface-water productivity (as derived from the ratio between heterotrophic and autotrophic dinocysts) remained generally low throughout the studied interval. Notably, this ratio does not exhibit any correlation with changes in surface-water temperature, which is estimated from the ratio of warm-water over cold-water dinocysts. Together with the consistently low surface-water productivity, the lack of a correlation between surface-water productivity and temperature makes it highly unlikely that the observed paleoceanographic change was caused by a southward migration of the Arctic Front. Instead, we argue that our data may document an enhanced influence of the (Proto-) Labrador Current on surface waters offshore Newfoundland during the earliest Miocene that suppressed the influence of the Gulf Stream in this region of the Northwest Atlantic. We speculate that the enhanced influence of the (Proto-) Labrador Current was triggered by cooling of the northern hemisphere and possibly modulated by high-latitude sea-ice expansion.
Available onlie 21 November 2017
Gesehen am 01.02.2018